Improved Delay-and-Sum Beamforming Algorithm for Breast Cancer Detection. (5th June 2008) - Klemm, M.; Craddock, I. J.; Leendertz, J. A.; Preece, A.; Benjamin, R.
Abstract : We have evaluated a modified delay-and-sum (DAS) beamforming algorithm for breast cancer detection with a microwave radar-based system. The improved DAS algorithm uses an additional weight factor calculated at each focal point to improve image quality. These weights essentially represent the quality of preprocessing and coherent radar operation. Using a multistatic UWB radar system based on a hemispherical antenna array, we present experimental detection of 7 mm and 10 mm phantom tumours. We show that the new proposed DAS algorithm improves signal-to-clutter ratio in focused images by 2.65 dB for 10 mm tumour, and by 4.4 dB for 7 mm tumour.